Analysis and Simulation of Load Unbalance of Distribution Transformer Feeder Lk.10 in ULP Medan City - Sam, Jihan Fadillah; Rahmaniar, Rahmaniar; Gunawan, Haris (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
Load imbalance in three-phase distribution transformers leads to high neutral currents, increased power losses, and decreased system efficiency. This study aims to analyze and simulate load imbalances on distribution transformers located on Feeder LK.10 at PT PLN (Persero) ULP Medan Kota. Data collection was conducted through field measurements of voltage and current, followed by manual calculations and simulations using ETAP 19. The analysis focused on load imbalance percentage, transformer loading, neutral current, and power losses. Results indicate that several transformers exhibit critical imbalance conditions, with some exceeding 25% load imbalance and significant neutral current. The ETAP 19 simulation results show a high level of accuracy compared to actual field measurements, with an average error below 3%. This study confirms that accurate monitoring and proper load redistribution are essential to maintain distribution transformer performance. The findings are expected to support PLN in improving power quality and reliability in distribution systems.